BLINATUMOMAB IN PEDIATRIC ACUTE LYMPHOBLASTIC LEUKEMIA: MECHANISM OF ACTION, CLINICAL RELEVANCE, AND EMERGING THERAPEUTIC PERSPECTIVES - Jachimczak, Ewa; Gąsiorowska, Vanessa; Jaruga, Paulina; Grodkowska, Karolina; Wojtanowska, Ewa; Kozicka, Julia; Paczyna, Julia; Mazur, Marcin; Smyczyńska, Natalia; Michalak, Mateusz (International Journal of Innovative Technologies in Social Science, 2026)
Acute lymphoblastic leukemia (ALL) is the most common malignancy in children, and despite significant improvements in survival with intensive chemotherapy, relapse and minimal residual disease (MRD) remain major clinical challenges. Blinatumomab is a bispecific T-cell engager (BiTE) antibody targeting CD19-positive B-cell precursor ALL. By simultaneously binding CD3 on T lymphocytes and CD19 on leukemic cells, it enables major histocompatibility complex (MHC)-independent activation of cytotoxic T cells and targeted elimination of malignant cells. Clinical studies have demonstrated that blinatumomab is effective in inducing remission in relapsed or refractory pediatric ALL and in achieving molecular remission in MRD-positive patients. Compared with conventional chemotherapy, it shows improved efficacy and a more favorable toxicity profile, although cytokine release syndrome and neurotoxicity remain clinically relevant adverse events. Blinatumomab is increasingly used as a bridge to hematopoietic stem cell transplantation and is being investigated in combination regimens and earlier treatment settings. However, therapeutic resistance, including CD19 antigen loss and T-cell dysfunction, remains a limitation. Overall, blinatumomab represents a significant advancement in immunotherapy for pediatric ALL, bridging conventional chemotherapy and cellular therapies such as CAR-T.